2014
DOI: 10.1017/s0968565014000237
|View full text |Cite
|
Sign up to set email alerts
|

Public or private interests? The investment behaviour of public officials in Antwerp during the early modern period

Abstract: Indebted cities were a widespread phenomenon during the Ancien Régime. However, some found ways to innovate the management of their municipal debt, whilst others fell prey to over-indebtedness or default. In this article we have left the success stories aside and focused on the latter. Using early modern Antwerp as a case study, we have disentangled the underlying mechanisms that ultimately lead to over-indebtedness and (in some cases) default. Whilst the economic climate and the relationship between city and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Yet a recent analysis by De Vijlder and Limberger, published in this journal, suggests exactly the opposite (De Vijlder and Limberger 2014). Starting from the case of Antwerp, they argue that the town council abstained from purchasing urban annuities during the height of the Spanish War of Succession, and provided barely 5 per cent of the total investment (De Vijlder and Limberger 2014, p. 318). It seems logical to assume that town magistrates had similar goals in Dordrecht and Antwerp, namely to try to earn as much profit as possible in the market for urban public debt.…”
Section: IImentioning
confidence: 93%
See 1 more Smart Citation
“…Yet a recent analysis by De Vijlder and Limberger, published in this journal, suggests exactly the opposite (De Vijlder and Limberger 2014). Starting from the case of Antwerp, they argue that the town council abstained from purchasing urban annuities during the height of the Spanish War of Succession, and provided barely 5 per cent of the total investment (De Vijlder and Limberger 2014, p. 318). It seems logical to assume that town magistrates had similar goals in Dordrecht and Antwerp, namely to try to earn as much profit as possible in the market for urban public debt.…”
Section: IImentioning
confidence: 93%
“…82–3). Later, during the seventeenth century, members of the Antwerp council accounted for 22 per cent of the investors and for 31 per cent of the investment in the urban public debt (De Vijlder and Limberger 2014, pp. 317–19).…”
mentioning
confidence: 99%
“…In this regard, Stasavage has suggested that small-scale oligarchic polities had an enormous advantage when furthering public credit, because of the short distances to decision making (2011, p. 2). Numerous other towns failed to establish secure public credit, however; and Florentine creditors continued to believe in the myth of their infallible funded public credit, despite being confronted by obvious signs of decline (Veseth 1991, p. 199; De Vijlder and Limberger 2014).…”
Section: IIImentioning
confidence: 99%
“…Smith (2021) and Baguet (2016) focused on the investment choices made by individuals, stressing the importance of family, social and civic networks in the investment processes either in the East Indian Company or in Ghent's municipal debt. Except for Shammas (2020), Gelderblom and Jonker (2009, 2011) and De Vijlder and Limberger (2014), studies have failed to understand institutional investors' investment behaviour during the Old Regime. Examining the donors and trustees enrolled in the Charity Commission Report for England and Wales, Shammas (2020) observed a long-term shift from real estate investments into perpetual government annuities in the mid-18 th century, mainly driven by legal changes.…”
Section: Introductionmentioning
confidence: 99%